Learning analytics leading to remote invigilation for eTests: A case study - Baird, Michael; Sefcik, Lesley; Steyn, S.; Price, C. (Springer, 2018)
This volume offers new research in such learning analytics and demonstrates how they support students at institutions of higher education by offering personalized and adaptive support of their learning journey.